2011
DOI: 10.1175/2010mwr3615.1
|View full text |Cite
|
Sign up to set email alerts
|

The GloSea4 Ensemble Prediction System for Seasonal Forecasting

Abstract: Seasonal forecasting systems, and related systems for decadal prediction, are crucial in the development of adaptation strategies to climate change. However, despite important achievements in this area in the last 10 years, significant levels of skill are only generally found over regions strongly connected with the El Niño–Southern Oscillation. With the aim of improving the skill of regional climate predictions in tropical and extratropical regions from intraseasonal to interannual time scales, a new Met Offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
155
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 50 publications
5
155
1
1
Order By: Relevance
“…Repairs to damaged homes, businesses and flood defences were required, and procedures for forecasting and mitigating the floods are understandably being examined. Until relatively recently, a lack of skill in seasonal weather forecasts in extratropical regions beyond a lead time of 1 month (Lavers et al, 2009;Arribas et al, 2011) discouraged the development of routine seasonal hydrological forecasts using a climate model output in Britain. However, the potential for seasonal hydrological forecasting in the UK is now being explored.…”
Section: Introductionmentioning
confidence: 99%
“…Repairs to damaged homes, businesses and flood defences were required, and procedures for forecasting and mitigating the floods are understandably being examined. Until relatively recently, a lack of skill in seasonal weather forecasts in extratropical regions beyond a lead time of 1 month (Lavers et al, 2009;Arribas et al, 2011) discouraged the development of routine seasonal hydrological forecasts using a climate model output in Britain. However, the potential for seasonal hydrological forecasting in the UK is now being explored.…”
Section: Introductionmentioning
confidence: 99%
“…The UM is used for weather forecasting as well as seasonal forecasting (with GloSea systems [38,39]) and climate modelling (HadGEM1, HadGEM2-ES and HadGEM3 as discussed in §3). The various modelling systems are listed in appendix A.…”
Section: Using Seamless Prediction To Unlock Drivers Of High Latitudementioning
confidence: 99%
“…Climate models also show that summer ice loss depends strongly on winter ice thickness [30,44] which suggests that if seasonal forecasts can be initialized with accurate sea ice conditions, there is a good opportunity to predict summer sea ice extent several months ahead. Peterson et al [45] have shown that the GloSea4 system [38], which is also based on the UM, has predictive skill for the September sea ice extent with a six month lead time. Figure 4 shows the predictions of September sea ice from GloSea5 (initialized in April), which shows the skill in the hindcast as well as the skill in the 2013 ensemble forecast.…”
Section: Using Seamless Prediction To Unlock Drivers Of High Latitudementioning
confidence: 99%
See 1 more Smart Citation
“…A variety of methods have been proposed to convert ensemble outputs to calibrated probabilistic forecasts of future meteorologic variables such as temperature and precipitation [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The workflow for applying, assessing and comparing the performance of different methods involves many steps: downloading historic observations and ensemble outputs; applying the selected methods to produce probabilistic forecasts; comparing the performance of the selected methods over a common past period using any of several possible metrics; and producing summary graphics.…”
Section: Introductionmentioning
confidence: 99%